CanSAR: update to the cancer translational research and drug discovery knowledgebase. Issue Volume 47:Issue D1(2019) (28th November 2018) - Coker, Elizabeth A; Mitsopoulos, Costas; Tym, Joesph E; Komianou, Angeliki; Kannas, Christos; Di Micco, Patrizio; Villasclaras Fernandez, Eloy; Ozer, Bugra; Antolin, Albert A; Workman, Paul; Al-Lazikani, Bissan
Abstract: canSAR (http://cansar.icr.ac.uk ) is a public, freely available, integrative translational research and drug discovery knowlegebase. canSAR informs researchers to help solve key bottlenecks in cancer translation and drug discovery. It integrates genomic, protein, pharmacological, drug and chemical data with structural biology, protein networks and unique, comprehensive and orthogonal 'druggability' assessments. canSAR is widely used internationally by academia and industry. Here we describe major enhancements to canSAR including new and expanded data. We also describe the first components of canSAR black —an advanced, responsive, multi-device compatible redesign of canSAR with a question-led interface.